Answer:
center is (2,-3)
Radius =
![√(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ioc94yndeogljnfffe39yptishjhrbwo38.png)
Explanation:
![2x^2-8x+2y^2+12y+14=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bqrbs2xeyxo1kr6pl1aod1chrr1v4bwrc4.png)
To find out the center and radius we write the given equation in
(x-h)^2 +(y-k)^2 = r^2 form
Apply completing the square method
![2x^2-8x+2y^2+12y+14=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bqrbs2xeyxo1kr6pl1aod1chrr1v4bwrc4.png)
![(2x^2-8x)+(2y^2+12y)+14=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lzhuzt6ei6stspnzd2o3x6bvnlok3bajzo.png)
factor out 2 from each group
![2(x^2-4x)+2(y^2+6y)+14=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ffkx3y2ad6l1mve1oqfoz3i25ehjicp43c.png)
Take half of coefficient of middle term of each group and square it
add and subtract the numbers
4/2= 2, 2^2 = 4
6/2= 3, 3^2 = 9
![2(x^2-4x+4-4)+2(y^2+6y+9-9)+14=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v2mcf2l9mh467lfd38xsueczjyzh3h5wrt.png)
now multiply -4 and -9 with 2 to take out from parenthesis
![2(x^2-4x+4)+2(y^2+6y+9)+14-8-18=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/olcw7hh9wqpsk2bjv8xop00k2pb7maos8j.png)
![2(x-2)^2 +2(y+3)^2 -12=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2wps6phr1q4nafk7hgkmwpq2rl3qzccm0o.png)
Divide whole equation by 2
![(x-2)^2 +(y+3)^2 -6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ojqmzl9ne5xbzbqw3w32pnr90domb1aejk.png)
Add 6 on both sides
![(x-2)^2 +(y+3)^2 -6=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ojqmzl9ne5xbzbqw3w32pnr90domb1aejk.png)
now compare with equation
(x-h)^2 + (y-k)^2 = r^2
center is (h,k) and radius is r
center is (2,-3)
r^2 = 6
Radius =
![√(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ioc94yndeogljnfffe39yptishjhrbwo38.png)